Metabolism of parathyroid organoids - Sekhar, Konjeti R.; Codreanu, Simona G.; Williams, Olivia C.; Rathmell, Jeffrey C.; Rathmell, W. Kimryn; McLean, John A.; Sherrod, Stacy D.; Baregamian, Naira (Frontiers in Endocrinology, 2023)
We successfully developed a broad spectrum of patient-derived endocrine organoids (PDO) from benign and malignant neoplasms of thyroid, parathyroid and adrenal glands. In this study, we employed functionally intact parathyroid PDOs from benign parathyroid tissues to study primary hyperparathyroidism (PHPT), a common endocrine metabolic disease. As proof of concept, we examined the utility of parathyroid PDOs for bioenergetic and metabolic screening and assessed whether parathyroid PDO metabolism recapitulated matched PHPT tissues. Our study methods included fine-needle aspiration (FNA)-based technique to establish parathyroid PDOs from human PHPT tissues (n=6) in semi-solid culture conditions for organoid formation, growth, and proliferation. Mass spectrometry metabolomics analysis of PHPT tissues and patient matched PDOs, and live cell bioenergetic profiling of parathyroid PDOs with extracellular flux analyses were performed. Functional analysis cryopreserved and re-cultured parathyroid PDOs for parathyroid hormone (PTH) secretion was performed using ELISA hormone assays. Our findings support both the feasibility of parathyroid PDOs for metabolic and bioenergetic profiling and reinforce metabolic recapitulation of PHPT tissues by patient matched parathyroid PDOs. Cryopreserved parathyroid PDOs exhibited preserved, rapid, sustained secretory function after thawing. In conclusion, successful utilization of parathyroid PDOs for metabolic profiling further affirms feasibility of promising endocrine organoid platforms for future metabolic studies and broader multiplatform and translational applications for therapeutic advancements of parathyroid and other endocrine applications.